Sorption of Coated and Uncoated Nanocrystalline Zinc Oxide from Aqueous Solutions onto Raw and Acetylated Cellulose Sago Hampas: Equilibrium, Kinetic and Thermodynamic Studies - Droepenu, Eric Kwabena (Trans Tech Publications Ltd, 2021)
In this study, sorption efficiency of coated (C-) and uncoated (U-) zinc oxide nanoparticles (ZnO-NPs) in aqueous solution onto raw sago hampas (RSH) and acetylated sago hampas (ACSH) was studied. Physical and chemical characteristics of both the sorbate and sorbents were analysed using various characterization techniques. The mechanism of the sorption process was evaluated using equilibrium isotherms, kinetic and thermodynamic studies. From the study, maximum percentage removal of both sorbate ions were achieved at an equilibration time of 100 minutes with an optimum sorbate mass of 2.0 g per 50 ml. The study recorded a maximum % removal of 85.1% & 87.6% for C-and U-ZnO-NPs (< 50 nm) onto RSH and 90.0% & 91.1% onto ACSH. Langmuir isotherm fitted well for the sorption process with the highest efficiency of 0.793 mg/g recorded for C-ZnO-NPs onto RSH. Pseudo-second model best described the sorption process. An exothermic and non-spontaneous sorption process was realised in all the sorption studies except that of U-ZnO-NPs (< 50 nm) onto ACSH which became spontaneous as temperature increased. Based on the findings from the multiple approaches employed, both sorbents could be proposed as viable alternatives to act as a green sorbent in the removal of ZnO-NPs from water and wastewater.